Concrete STRENGTH DEVELOPMENT OF HIGH STRENGTH CONCRETE MADE WITH RECLAIMED AGGREGATE : STRENGTH DEVELOPMENT OF HIGH STRENGTH CONCRETE MADE WITH RECLAIMED AGGREGATE - Hasan, Md. Rakibul (การประชุมวิศวกรรมโยธาแห่งชาติครั้งที่ 26, 2021)
This paper aimed at evaluating the efficiency of using the reclaimed aggregate in fresh concrete without taking any special measures. Normally recycled concrete aggregates mainly come from the construction site or demolition waste. The production process of the recycled concrete aggregate is followed by two steps – crushing and screening process. The recycling and reuse of aggregates save natural resources and decrease construction costs without compromising the strength and durability properties. Concrete used for making recycled concrete aggregate as a replacement of conventional aggregate in concrete was collected from the construction site, Mahidol University, Kanchanaburi campus. Aggregate tests were conducted to analyze the properties of natural aggregate and recycled concrete aggregate. The concrete mixes were prepared of 40 MPa, 50 MPa, and 60 MPa grade respectively with different W/C ratio and the recycled concrete aggregate was replaced with different percentages (0%, 25%, 50%, 75%, and 100%) with natural aggregate to evaluate the strength and durability properties. The main purpose of this study is to compare different properties of natural aggregate and recycled concrete aggregate and also compare the compressive strength of concrete made with natural aggregate and recycled concrete aggregate. The experimental results showed that some properties of the recycled concrete aggregates vary from natural aggregates and there was not much difference in compressive strength of concrete made with natural aggregate and recycled concrete aggregate.